Investigating Links Between Fear of COVID-19, Neuroticism, Social Networks Use Disorder, and Smartphone Use Disorder Tendencies - Montag, Christian; Sindermann, Cornelia; Rozgonjuk, Dmitri; Yang, Shixin; Elhai, Jon D.; Yang, Haibo (Frontiers in Psychology, 2021)
The present study investigates links between Fear of COVID-19, the personality trait of neuroticism, social networks and smartphone use disorder (SNUD and SmUD, respectively) tendencies. In an online survey, N = 932 participants recruited at a Chinese university (237 males and 695 females) completed self-reports on Fear of COVID-19, neuroticism (and other personality traits from the Big Five Inventory-44; BFI-44), the Bergen Social Media Addiction Scale (assessing tendencies toward SNUD) and Smartphone Addiction Scale short version - assessing individual differences in tendencies towards SmUD. Our findings showed that all variables were positively correlated with each other. A mediation model suggested that SNUD (in parts) mediated the association between Fear of COVID-19 and SmUD. Although neuroticism was robustly correlated with all mentioned variables, no moderation effect could be observed on the investigated Fear-of-COVID-19-SNUD-link. The findings of this work provide further evidence that the smartphone itself is only a device giving individuals access to software applications, which then might be excessively used. Beyond that, the present data indicate neuroticism to be a risk factor with respect to Fear of COVID-19, SNUD and SmUD, although the study is limited by its cross-sectional study design.